TINJAUAN YURIDIS TINDAKAN SPAMMING BERKONTEN PORNOGRAFI DALAM HUKUM PIDANA INDONESIA - Dita Amelia; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Spammingpornographic content is a form of message sent via electronic device that is sent continuously and the content is not wanted by the recipient and contains pornographic content, the pornography in question is images, sketches, writing, sounds, moving pictures, animation, cartoons, conversations, gestures, or other messages through various forms of communication media and public performances, which contain obscenity or sexual exploitation that violates the norms of decency in society. The purpose of writing this thesis, namely; First, the regulation on spamming with pornographic content in Indonesian criminal law. Second, analyzing criminal law enforcement in overcoming pornographic content spamming.This type of research used in this research is a type of normative legal research or it can also be called literature research. Normative juridical research discusses doctrines or principles in legal scienceFrom the research, there are two main points that can be concluded. First, The regulation on spamming with pornography in Indonesian criminal law, that the regulation of spamming with pornographic content through the internet in Indonesian criminal law can be charged under Pasal 27 ayat (1) Undang-Undang Nomor 19 Tahun 2016 tentang Perubahan Atas Undang-Undang Nomor Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik as a special rule (lex specialis). Second, criminal law enforcement in overcoming pornographic content spamming, that criminal law enforcement in tackling pornographic content spamming can be done by implementing several strategies, namely improving the quality of human resources in law enforcers, especially cyber crime investigators, public legal awareness education to report to the Police, completed with electronic message evidence received by the victim.Keywords: Spamming, Decency, Criminal Law